Substâncias para prevenção de neuropatia periférica relacionada à quimioterapia antineoplásica: revisão integrativa - Magalhães, Tayanne de Lima (2018)
Antineoplastic chemotherapy (QT) consists of the use of drugs that interfere with cell reproduction, in the fight against malignant cells, but can also affect healthy cells, causing several side effects (CE) that impair the continuity of treatment and the prolongation of life with quality. One such CD is peripheral neuropathy, which can cause harm to patients' treatment and quality of life. Thus, there is an incessant search in the field of oncology for the discovery of drugs that reduce the side effects caused by chemotherapy and in addition it is important that the nurse has access to the scientific evidence that consolidates the effective substances in the prevention of chemotherapy. To analyze in the literature scientific evidence on the effective substances for prevention of peripheral neuropathy induced by chemotherapy (NPIQ) in adult cancer patients submitted to antineoplastic chemotherapy. Integrative literature review, carried out in the databases Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature on Line (MEDLINE), SCOPUS, Latin American and Caribbean Literature in Health Sciences (LILACS), and Cochrane Library (COCHRANE). Data were collected using an instrument developed by the author, using the scale of the Oxford Center for Evidence-Based Medicine in the classification of the level of evidence. Already in the analysis of the methodological quality of the studies was used the scale of Jadad et al (1996). Nine articles of the type randomized clinical trial with good methodological quality were included. The substances with recognized efficacy for prevention of NPIQ were TJ-107, glutathione, neurotropin and ganglioside-monosialic acid. On the other hand, vitamin B and E, alpha lipoic acid, had no proven efficacy. Regarding the calcium / magnesium compound, there was divergence in the outcome of the studies. Since NPIQ is a side effect with incidence and associated significant prevalence in cancer patients submitted to chemotherapy, it is necessary to invest more in research in this area of study, especially in Brazil, where no study with a good level of scientific evidence for prevention was found of the NPIQ.